Institutional Framework for the Development of the Tourism Market - Alimova Mashhura Toirxonovna; Umarov Tohir Obloqulovich; Inoyatillo Ismatilloyevich Tuychiev (Universitas Muhammadiyah Sidoarjo, 2020)
The article examines the institutional basis of the tourism market development based on the scientific and theoretical analysis of the essence and content of the concept of «Institute». A brief description of the normative-legal documents and organizations regulating socio-economic relations and processes at the International and national level in the market of tourism have been mentioned. To increase the competitiveness of national tourist organizations in the international tourism market, a proposal was developed for the establishment of non-governmental associations of tourist organizations operating in the region, namely the Union of members of the regional tourist cluster, as well as proposals and recommendations for improving the institutional framework of cooperation in the field of Tourism.